2014
DOI: 10.1039/c4fo00452c
|View full text |Cite
|
Sign up to set email alerts
|

Hericium erinaceus (Bull.: Fr) Pers. cultivated under tropical conditions: isolation of hericenones and demonstration of NGF-mediated neurite outgrowth in PC12 cells via MEK/ERK and PI3K-Akt signaling pathways

Abstract: Hericium erinaceus (Bull.: Fr.) Pers. is an edible and medicinal mushroom used traditionally to improve memory. In this study, we investigated the neuritogenic effects of hericenones isolated from H. erinaceus and the mechanisms of action involved. H. erinaceus was cultivated and the secondary metabolites were elucidated by high performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC-MS), and nuclear magnetic resonance (NMR). The secondary metabolites were tested for neurite outgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
76
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 46 publications
8
76
1
Order By: Relevance
“…In the presence of 5 ng/mL of NGF, hericenones significantly increased the percentage of neurite-bearing cells compared with control cell, which had either hericenones alone or 5 ng/mL of NGF. 12 In contrast to this result, a polysaccharide purified from H. erinaceus mycelium enhanced neurite outgrowth of PC-12 cells, and…”
contrasting
confidence: 43%
See 2 more Smart Citations
“…In the presence of 5 ng/mL of NGF, hericenones significantly increased the percentage of neurite-bearing cells compared with control cell, which had either hericenones alone or 5 ng/mL of NGF. 12 In contrast to this result, a polysaccharide purified from H. erinaceus mycelium enhanced neurite outgrowth of PC-12 cells, and…”
contrasting
confidence: 43%
“…Our previous findings showed that Hericenone E isolated from H. erinaceus increased the phosphorylation of extracellular-signal regulated kinases and protein kinase B, potentiating nerve growth factor (NGF)-induced neuritogenesis in PC-12 cells via the MEK/ERK and PI3K/Akt pathways. 12 Similarly, Erinacine D isolated from the mycelium of H. erinaceus acted as a stimulator of NGF synthesis. 13 Because of the poor regenerative capacity of CNS, other methods like drugs, gene therapy, stem cells therapy, and nanotechnology continue to be very active with significant clinical potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phan et al (2014) isolated four benzyl alcohol derivatives namely hericenones B-E from the fruit bodies of H. erinaceus cultivated in tropical conditions in Malaysia. Hericenone E exerts neurotrophic activity in PC12 cells, and this activity is mediated by extracellular signal-regulated kinase 1/2 (ERK1/2) and phosphoinositide-3-kinase/protein kinase B (PI3K/Akt) signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The mushroom has been extensively tested in in vitro trials as the neurite outgrowth stimulator in the cultured cells of neural hybrid clone NG108-15 and rat phechromocytoma PC12 in our Fungal Biotechnology laboratory, Mushroom Research Centre, Faculty of Science (Wong et al, 2007;Lai et al, 2013;Phan et al, 2014). Phan et al (2014) isolated four benzyl alcohol derivatives namely hericenones B-E from the fruit bodies of H. erinaceus cultivated in tropical conditions in Malaysia.…”
Section: Introductionmentioning
confidence: 99%